Food for love: the role of food offering in empathic emotion regulation - Hamburg, Myrte E.; Finkenauer, Catrin; Schuengel, Carlo (Frontiers in Psychology, 2014)
The present article examines the interpersonal and intrapersonal antecedents and consequences of food offering. Food offering is one of the earliest biobehavioral regulatory interactions between parent and child. It ensures survival of the child who is fully dependent on food provision by others. The quality of these early interactions influences how people respond to situations later in life, and food offering in particular may be closely related to emotion regulation throughout the lifespan. While research has examined other forms of emotion regulation, and food consumption has been studied from an intrapersonal perspective, we know little about the interpersonal effects of food offering. After reviewing literature from a wide range of disciplines, we propose that one mechanism underlying these effects is empathic emotion regulation (EER). We conceptualize EER as an interpersonal regulation system in which an empathic response to another person’s emotional state aims to regulate both emotion within the provider and across interaction partners. We suggest that the offer of food by an empathic provider is motivated by the emotional state of one’s interaction partner (recipient). By offering food, the provider not only aims to attenuate the recipient’s negative affect but also her own. Food offering thereby becomes a means to increase positive affect for both recipient and – when the offer has the desired effect – provider. We further propose that the sharing of food resources as well as the use of food as a support behavior increases interpersonal closeness. Finally, we frame the process of food offering within a developmental perspective. If the regulatory success of food offering becomes a replacement for other support behaviors, children will learn from an early age to use food as a primary means to soothe self and others, possibly resulting in eating disorders and a restricted range of coping behavior.